MANAGEMENT AND COUNSELLING OF THE AGED: NIGERIA AS A CASE STUDY - OYETADE, Monilola Dasola (Ilorin Journal of Education, 2023)
This study examined the concept of ageing, related issues in ageing and therapies that counsellors can adopt in managing the senescence and related complications. This study is exploratory and qualitative in nature, and was based on information gathered from an expert working in a geriatric centre. Various issues associated with global ageing population stems from attributes and beliefs that growing old could be accompanied by loss of competence, intellectual deterioration and discrimination. The increase in life expectancy worldwide due to some improvements in health facilities and low mortality rate among others, accounts for the increase in the population of the Aged. Many elderly people in Nigeria experience abuse, psychosocial issues, health problems and disability. Similarly, the burden of these problems rest on the society and this could be demanding in the area of economic growth, patterns of work, retirement and family dependency, to mention a few. Therefore, the place of counselling cannot be overemphasized if the elderly in the society will continue to enjoy quality and active life. It is therefore recommended, that Nigerian government should come up with a functional national policy that will include counselling services in all elderly institutions which will be managed by Professional counsellors.